The psychological depression response of Iraqi subfertile wives :a descriptive study: no - mohsin, mousa (Karbala Journal of Medicine, 2022)
Worldwide about 15% in the childbearing years have subfertility problems. [1] Many studies demonstrated that men and women have abnormal emotional responses, such as stress, anxiety and depression. Around 5% of couples living in the developed countries experience primary subfertility (inability to have any children or secondary subfertility. [1] Experts say that only half of all subfertility cases had a physical origin, the rest were unexplained. But researcher notice that most cases of subfertility attributed to physiological cause in the man or woman. About one-third from those physiological problems is identified in the woman, one-third in the man, and about one-tenth of the time in both. Half of the women and 15% of the men said that infertility was the most upsetting experience of their lives. [2] In Iraq and because of the social regulations and ideas about the female and male thinking the females was under huge psychological pressure towered the pregnancy. In our community less research to examine both men’s and women’s reactions to subfertility, men’s tend to report experiencing less distress than women. When the problem is diagnosed in their wives, men do not report being as distressed as the women do. Treat infertility by more advanced assisted reproductive technology such as in vitro fertilization (IVF) studies suggest that they may also add to the stress, anxiety, and grief that patients are already experiencing from infertility itself. Aim: The purpose of this study was to evaluate the prevalence of psychological stress (depression) experienced by subfertile wives Material and methods: DESIGN: Cross-sectional prospective study held in between March 2018 until March 2020 SETTING: Face-to-face and online interviews were conducted in study participants PARTICIPANTS:498 subfertile women were interviewed all suffering from primary or secondary infertility only 433 of them were accept to participating in our study and answered the questionnaire they are from subfertility units in maternity hospitals in Kerbala, Najaf and Babylon and in privet clinics and on social media METHODS: A structured questionnaire were used and filled by direct interviewed and/or by social media chatting MAIN OUTCOME MEASURES: The correlation between depression score and subfertility RESULTS: The prevalence of depression was very high among infertile women in Kerbala, Najaf and Babylon/Iraq, where 93.5% were depressed